NIR-II fluorescence lymphatic imaging and intraoperative navigation based on the "isolated cage" monodisperse strategy. (April 2023) - Qi, Shaolong; Wang, Yajun; Zhu, Youliang; Zhang, Xueyan; Wang, Xinyu; Yu, Xinyang; Yang, Kai; Bai, Bing; Feng, Yunxuan; Lei, Jiaqi; Zhang, Kuo; Lu, Zhongyuan; et al.
Abstract: Fluorescence imaging in the second near-infrared (NIR-II) window is well suited for biological systems due to lower tissue scattering and micrometer-scale resolution at depths of millimeters. Unfortunately, none of the NIR-II fluorophores have clinical application due to low quantum yields, poor photostability, and long-term biosafety concerns. Herein, we develop NIR-II fluorescent nanoprobes based on the "isolated cage" monodisperse strategy, which significantly inhibits the π-π stacking interactions and restricts internal rotation of the arrested indocyanine green (ICG) fluorophores, which minimizes aggregation-caused quenching and enhances their NIR-II imaging performance. Unlike ICG's imaging window of several minutes, the nanoformulations have reduced photobleaching and provide longer observation times. The increased imaging time allows high spatiotemporal resolution of blood vessels and lymphatic system. Benefiting from the high resolution and sensitivity of the nanoprobes, sentinel lymph nodes are accurately removed under fluorescence navigation. More intriguingly, the patency of lymphovenous anastomosis (LVA) is presented more intuitively by qualitative and quantitative NIR-II fluorescence signals, which will directly benefit the innovation and promotion of LVA. Graphical Abstract: The "isolated cage" monodisperse strategy was introduced into nanoparticles to enhance the fluorescence quantum yield, temporal-spatial resolution, and photostability of ICG at NIR-II window, achieving successful applications in lymphatic imaging, SLNs navigation, and verification of LVA patency. ga1 Highlights: PCMI NPs are developed based on the "isolated cage" monodisperse strategy, which significantly minimizes aggregation-caused quenching of ICG fluorophores and enhances their NIR-II imaging performance. PCMI NPs could afford high spatiotemporal resolution of blood vessels and lymphatic system imaging in vivo . The patency of lymphovenous anastomosis (LVA) is presented more intuitively by qualitative and quantitative NIR-II fluorescence signals of PCMI NPs.